Intention to Hire Older Workers: A Predictive Model - Lau, Claudia; Choong, Chee Keong; Wong, Kee Luen (European Publisher, 2019)
Malaysia is currently facing a serious labour shortage as a result of declining employment participation rate from its ageing population. Nevertheless, the utilisation of skilful and experienced older workers requires the willingness of business organizations to hire them. Therefore, this paper examines managers’ intention to hire older workers by using an extended model of the Theory of Planned Behaviour (TPB). Past experience is an additional variable used beside attitude, subjective norm and perceived behavioural control in the TPB. A quantitative method of research is adopted through 55 well-prepared questionnaires. The model and hypotheses are tested using partial least square - structural equation modelling analysis. The result of the survey involved 468 hiring managers from 11 industries and 9 states in Malaysia. The research model accounted for a moderate portion of the variance in future hiring intention (R2=0.392). The findings suggest that the predictive component of attitude, subjective norm, and perceived behavioural control are related to the future hiring intention whereas the past experience predictor found no relation. This study's result makes a valuable theoretical contribution as it positioned at age discrimination on the employment of older workers, and serves to future research with reasonable modification on the areas. This study has practical implication at two-levels: bring awareness to business organizations on ageing workforce and preparatory actions on good workplace practices to eliminate inequalities in the age-diversified workforce.